Towards a model of talent development in physical education - Bailey, R.; Morl, D. (Sport, Education and Society, 2006)
Traditional conceptions of talent generally emphasise the construction of threshold values and the development of relatively unitary abilities, and this approach still dominates talent development programmes for elite sport. Most researchers on high ability, however, now favour domain-specific, multidimensional conceptions of ability that stress the development of behavioural potential and its interaction with personal and environmental characteristics. This paper presents a model of talent in physical education, drawing together findings from a wide range of literature on the realisation and inhibition of abilities, international studies of effective school-based identification and provision strategies, and a conception of the subject as an integration and realisation of different forms of ability. In presenting this model, the authors aim to redress the imbalance within the current debate from an almost total concern with out-of-school clubs and the preparation for adult elite sport, in favour of a more equitable and inclusive approach, premised upon the unique importance of mainstream, curricular physical education within any talent development scheme.